2020
DOI: 10.1183/16000617.0011-2020
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection withPseudomonas aeruginosaandAspergillus fumigatusin cystic fibrosis

Abstract: ObjectivesCystic fibrosis (CF) lung disease is characterised by mucus stasis, chronic infection and inflammation, causing progressive structural lung disease and eventual respiratory failure. CF airways are inhabited by an ecologically diverse polymicrobial environment with vast potential for interspecies interactions, which may be a contributing factor to disease progression. Pseudomonas aeruginosa and Aspergillus fumigatus are the most common bacterial and fungal species present in CF airways respectively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 131 publications
(159 reference statements)
0
27
0
Order By: Relevance
“…It is possible that strains may vary in other aspects, for example immunological escape from phagocytes [ 38 ], but this is beyond the scope of our epithelial focused study and there is no literature in this regard. Additionally, A. fumigatus strains isolated from adults with CF may display more variable immunostimmulatory capacity as a consequence of prolonged environmental adaptation and interactions with other CF microbes [ 39 ]. The summary for clinicians is that the presence of Aspergillus is more important to early CF lung pathology than the strain of Aspergillus and that typing should remain orientated to antifungal testing, ideally with a broader focus than the current azole testing.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that strains may vary in other aspects, for example immunological escape from phagocytes [ 38 ], but this is beyond the scope of our epithelial focused study and there is no literature in this regard. Additionally, A. fumigatus strains isolated from adults with CF may display more variable immunostimmulatory capacity as a consequence of prolonged environmental adaptation and interactions with other CF microbes [ 39 ]. The summary for clinicians is that the presence of Aspergillus is more important to early CF lung pathology than the strain of Aspergillus and that typing should remain orientated to antifungal testing, ideally with a broader focus than the current azole testing.…”
Section: Discussionmentioning
confidence: 99%
“…For selective isolation of Pseudomonas spp. we used Cetrimide agar with glycerol (BioLife, Italy) [5,9,12]. Salt agar (Farmaktiv, Ukraine) with egg-yolk emulsion (Hi-Media, India) was used for selective isolation of Staphylococcus aureus [13,15].…”
Section: Materials and Methods Of Researchmentioning
confidence: 99%
“…In cystic fibrosis patients, bacteria are predominant, and it has been demonstrated that Pseudomonas aeruginosa uses iron competition to inhibit A. fumigatus growth. In particular, this bacteria produces pyoverdine and pyochelin, iron chelators, and the bacteriophage Pf4, which inhibits fungal metabolism, but its effect could be overcome with ferric ion supplementation [ 91 ].…”
Section: Iron Metabolismmentioning
confidence: 99%